2017
DOI: 10.1111/dsji.12139
|View full text |Cite
|
Sign up to set email alerts
|

Do Technological and Course‐Related Variables Impact Undergraduates’ Perceived Favorability and Willingness to Recommend Online/Hybrid Business Courses?

Abstract: Lower teaching evaluations can affect students’ willingness to recommend an online course. To maintain online course quality, it is important to keep the “integrity” of a course, that is, offer to the extent possible, the same content and learning outcomes in an online course as the face‐to‐face (F2F) equivalent. This study explored the impact of background, technological, and course‐related variables on perceived favorability of online (versus F2F) courses and willingness to recommend courses using two indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Conscientious students may also have excellent time management and organization skills, thus lowering their anxiety toward online learning. In a study by Blau, Drennan Jr., Karnik, and Kapanjie (2017) , students who are well-prepared for an online class were found to perceive the course favorably, thus positively influencing their intention to recommend. They may also have a high sense of self-awareness, which has been found to play a positive role on individual participation in online learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…Conscientious students may also have excellent time management and organization skills, thus lowering their anxiety toward online learning. In a study by Blau, Drennan Jr., Karnik, and Kapanjie (2017) , students who are well-prepared for an online class were found to perceive the course favorably, thus positively influencing their intention to recommend. They may also have a high sense of self-awareness, which has been found to play a positive role on individual participation in online learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…Prior experience. Prior content knowledge, course format experience, or prior academic experience have been outlined as important for student success in both online (Blau et al, 2017;Estelami, 2014;Gering, Sheppard, Adams, Renes, & Morotti, 2018;Murph & Stewart, 2017) as well as in traditional face-to-face formats (Duff, 2004;Hailikari, Nevgi, & Komulainen, 2008;Martin, Wilson, Liem, & Ginns, 2013). Those who have successfully completed prior online courses evidence significantly higher course completion rates compared to students who have failed to complete a prior online course (Dupin-Bryant, 2004;Hachey et al, 2015).…”
Section: Racementioning
confidence: 99%
“…Course structure. Students' perceptions of the online learning environment and course structure have been highlighted as fundamental to student satisfaction as well as learning outcomes (Beach, 2018;Blau et al, 2017;Eom and Ashill, 2016;Galy, Downey, & Johnson, 2011;Gering, Sheppard, Adams, Renes, & Morotti, 2018). Students have reported that one of the most important factors for their success online is the course configuration, including easy access to materials, clear due dates, regular announcements, and distributed assignments (Beach, Stefanick and VanOverbeke, 2018;as cited in Beach, 2018).…”
Section: Course Factorsmentioning
confidence: 99%
“…Traditional students may have been more inclined to not like or not feel that the quality of an online course was equivalent to an in-person course. Blau, Drennan, Karnik and Kapanjie (2017) found a positive relationship between the number of online/hybrid courses taken by business students and perceived favorability of online (versus face-to-face) courses. Additional research investigating online course student perceptions, comparing traditional/on campus students taking an occasional online course versus completely online course students, should be studied.…”
Section: Study Limitations and Future Researchmentioning
confidence: 84%